Hearsay Evidence Admissibility: Due Process and Evidentiary Rules in Muslim Marriage Legalization (Isbat Nikah) - Latifatul Fajriyyah; Alfitri Alfitri (Universitas Lampung, 2022)
The hearsay evidence is still debated as valid witness evidence in Indonesian civil procedural law. Consequently, there is a disparity in judges’ decisions in handling religious civil cases when the evidence is from “hearsay witnesses.” A case in point is the decision on the application for marriage legalization issued by the Samarinda Religious Court, which received hearsay evidence, and the Samarinda Religious High Court, which rejected it. This paper intends to examine the judge’s considerations in accepting or rejecting hearsay evidence in marriage legalization applications to understand whether these considerations have used appropriate legal arguments per the principles of justice and legal certainty. As a normative-doctrinal legal study, this paper uses case law, statutory, and conceptual approaches in its discussion. It shows that the Samarinda Religious Court accepted hearsay evidence because they considered the exceptional circumstances of the marriage event that they wanted to prove. On the other hand, the Samarinda Religious Higher Court rejected the hearsay evidence because a “hearsay witness” could not be used in a contentious case. Even so, the two decisions have not provided clear legal arguments in accepting or rejecting the hearsay evidence. The development of procedural law jurisprudence in Indonesia opens up opportunities for its use in the evidentiary process to create justice and legal certainty for justice seekers.